Home Induction of Buprenorphine for Treatment of Opioid Use Disorder in Pregnancy. Issue 4 (October 2021) - Kelly, Jeannie C.; Raghuraman, Nandini; Stout, Molly J.; Russell, Sharman; Perez, Marta; Nazeer, Sarah; El Helou, Nicole; Zhang, Fan; Carter, Ebony
Abstract : Buprenorphine home induction for opioid use disorder in pregnancy is associated with high rates of treatment retention and adherence.